Airway analysis in skeletal Class I and Class II subjects with different growth patterns: A 2D cephalometric study - Swaroopa R Ponnada; Vivek R Ganugapanta; Kiran K Perumalla; Mohammed A Naqeed; T Harini; Shiva Praasad Mandaloju (Wolters Kluwer Medknow Publications, 2020)
Objective: A two-dimensional cephalometric study was carried out to assess the airway among individuals with Class I and Class II skeletal base. Materials and Methods: Class II subjects were further categorized into horizontal and vertical growers and average growth patterns to check the possible relationship between the facial skeleton and pharyngeal airway. Lateral cephalograms of 150 subjects were obtained using standard protocol in natural head position (NHP). Nasopharyngeal and oropharyngeal linear, and angular and nasopharyngeal area measurements were obtained using standardized tracing technique. Analysis of variance (ANOVA), level of significance, and post hoc Turkey's test were performed to assess the correlation between skeletal pattern of the individual and airway dimension. Gender discrimination was assessed using independent sample t test. Results: In linear measurements, significant differences were observed among upper pharynx (0.039), adenoid tissue 1 (0.036), and adenoid tissue 2 (0.01). In angular measurements, differences were observed with angle of nasopharynx (0.008). The nasopharyngeal area measurements were also associated with significant difference (0.038) with Class II vertical growers less than those with Class I average and Class II horizontal groups. Conclusion: Class II vertical growers had significantly reduced nasopharyngeal airways.